Dispersal Capacity of Trichogramma for the Management of Duponchelia fovealis - Pratissoli, Dirceu; Damascena, Alixelhe Pacheco; Oliveira, Regiane Cristina de [UNESP]; Carvalho, José Romário de; de Oliveira, Ana Carolina Lopes Francisco; Piffer, Ana Beatriz Mamedes; Pirovani, Victor Dias (MDPI, 2024)
The European pepper moth (Duponchelia fovealis) is predominant in the main strawberry production areas, including Brazil, as an important invasive pest and causes substantial damage to the crop. This damage is mainly attributed to the lack of effective management strategies. A promising alternative for managing this pest is implementing biological control through releasing natural enemies. This study determined the dispersal capacity of Trichogramma pretiosum for the management of D. fovealis in a strawberry crop in a low tunnel system 24, 48, and 72 h after parasitoid release. The experiments were carried out on strawberry farms in the mountainous region of Espírito Santo. Tunnels measuring 1.20 m wide by 50 m long were selected, in which artificial infestations of 30, 60, 90, and 120 eggs of D. fovealis were made on both sides of the strawberry tunnel at distances of 3, 7, 11, and 15 m, respectively, from the central point where the parasitoids were released. After the initial 24 h, new eggs were placed to replace the infested ones; the replacement was repeated at 48 and 72 h. The results indicated that, in strawberry plantations, T. pretiosum was efficient in parasitism. There was no difference between parasitism 24 and 48 h after parasitoid release, but parasitism was substantially lower after 72 h. The dispersion capacity of T. pretiosum was 14.21 linear meters, corresponding to an area of 17.05 m2. It is recommended that 93,000 T. pretiosum females be released per hectare every three days.
Keywords: biological control; egg parasitoid; strawberry; Trichogrammatidae